How do Online Learning Networks Emerge? A Review Study of Self-Organizing Network Effects in the Field of Networked Learning - Bieke Schreurs; Frank Cornelissen; Maarten De Laat (MDPI AG, 2019)
In this article we want to understand in more detail how learning networks emerge in online networked learning environments. An adage in Networked Learning theory is that networked learning cannot be designed; it can only be designed for. This adage implicitly carries the idea that networked learning is seen as learning in which information and communication technology is used to promote (emergent) connections between learners and their peers, learners and tutors and learners and learning resources. Emergence entails a self-organizing component. However, there is no comprehensive understanding of how self-organizing network effects occur in networked learning environments, how they influence possible learning outcomes and how these network effects can be enhanced or frustrated by the design elements of different networked learning environments. By means of a review we investigate how the three most known self-organizing network effects occur in networked learning environments, namely preferential attachment, reciprocity and transitivity. Results show that in most studies self-organizing network effects are significantly present. Moreover we found important (design) elements related to the people, the physical environments and the tasks of the learning networks that could influence these self-organizing network effects. Studies that looked at learning outcomes are limited. Based on the review study future research directions for the field of Networked Learning are addressed.